Diversity and structure of the stomatopod (Crustacea) community on the Amazon continental shelf - Silva,Kátia C. Araújo (2013)
The present study aimed to characterize the biodiversity of the Stomatopoda species found off the coast of the northern Brazilian states of Amapá and Pará, within the region's Exclusive Economic Zone. Two distinct sectors were surveyed, to the north and to the south of Cape Norte. The specimens were collected during fishery surveys carried out between 1996 and 1998 by the Revizee Program, using bottom shrimp trawl nets. The specimens were identified at the Crustaceans Laboratory of the Center for Research and Management of Fishery Resources of the Northern Coast and the Carcinology Laboratory of the Federal Rural University of Pernambuco. The 189 identified specimens represented Lysiosquilla scabricauda (Lamarck, 1818) (n = 2), Parasquilla meridionalis Manning, 1916 (n = 1), Squilla empusa Say, 1818 (n = 6), and Squilla lijdingi Holthuis, 1959 (n = 180). Only three species were collected in each of the survey sectors, with L. scabricauda and S. lijdingi being captured in both sectors. Squilla lijdingi was dominant in both sectors, whereas the other species were considered to be rare. Squilla lijdingi was very frequent in the northern sector, although the other stomatopods were infrequent. In the southern sector, L. scabricauda was sporadic, S. empusa was frequent, and S. lijdingi was very frequent. A significant difference was observed in the number of specimens captured in both sectors. The Shannon index was 0.6144 bits.ind-1 for the northern sector and 0.2708 bits.ind-1 for the southern one, whereas equitability was 0.3876 in the North and 0.1708 in the South. The stomatopods were collected at depths between 32 and 109 m, and were captured primarily on gravelly bottoms in the northern sector, and on muddy substrates in the southern sector. Stomatopods were more abundant in the northern sector during the dry season from June to November, whereas they were more common in the South during rainy season, from December to May.